Cucurak Tradition Before The Month Of Ramadan In Bogor West Java: Analysis Of Religious Values And Its Relevance To The Objectives Of Islamic Education - Amirah Nisrina Mumtaz; Lutfiah Ayundasari (At-Tarbiyat, 2024)
The Cucurak Tradition, which is still often found in the Bogor community when the month of Ramadan approaches, then raises the question of how religious values in the Cucurak Tradition. Considering that religious values are important to have, especially for the Indonesian nation whose society is heterogeneous. Therefore, researchers are interested in conducting a study to explore the religious value of the Cucurak Tradition carried out before the holy month of Ramadan and its relevance to the objectives of Islamic education. The research method used in this study is descriptive qualitative with a phenomenological approach. The discussion in this study includes the development of the Cucurak Tradition in Bogor, West Java, religious values in the Cucurak Tradition, and the relevance of religious values in the Cucurak Tradition to the objectives of Islamic education. This study concludes that the Cucurak Tradition as part of Sundanese culture has been attached to Islam, the implementation of the Cucurak Tradition as a form of joy in welcoming the arrival of the holy month of Ramadan, implemented by gathering and eating with the closest people. The Cucurak Tradition, which has been carried out for a long time, is currently experiencing changes in a number of aspects. The religious values contained in this tradition are silaturahmi, syukur, and tasamuh, and these values are in line with the objectives of Islamic education.